2006
DOI: 10.18553/jmcp.2006.12.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Antidiabetic Medications and Glycemic Control on Managed Care Organizations: A Review of the Literature

Abstract: regarding the impact of antidiabetic medications and glycemic control on the overall costs of care for patients with diabetes in U.S. managed care organizations (MCOs).SUMMARY: The pharmacy component accounts for typically 20% to 30% (full range, 10%-65%) of overall costs for MCO patients with diabetes. About 30% of pharmacy expenses are directly related to glycemic control, while the balance is spent on the management of macrovascular and microvascular complications related to diabetes and other common comorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 44 publications
(61 reference statements)
0
23
0
3
Order By: Relevance
“…14 In a systematic review of the literature (January 2000-November 2005) assessing the effect of antidiabetic medications and glycemic control on cost in patients with diabetes who were members of U.S. managed care organizations, investigators identified 8 studies showing that improved glycemic control reduces overall perpatient direct costs; of interest, the pharmacy component usually represented 20% to 30% of overall costs, and about 30% of pharmacy charges were directly correlated with glycemic control. 15 The current analysis was based on a hypothetical cohort of commercially insured and Medicare fee-for-service patients with type 2 diabetes who were identified from the NHANES database. Applying the United Kingdom Prospective Diabetes Study (UKPDS) complication risk model to the individual's risk characteristics, the analysis simulated diabetes complication rates under status quo risk factor profiles and complication reductions associated with improved management of A1c, BP, and lipids.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%
“…14 In a systematic review of the literature (January 2000-November 2005) assessing the effect of antidiabetic medications and glycemic control on cost in patients with diabetes who were members of U.S. managed care organizations, investigators identified 8 studies showing that improved glycemic control reduces overall perpatient direct costs; of interest, the pharmacy component usually represented 20% to 30% of overall costs, and about 30% of pharmacy charges were directly correlated with glycemic control. 15 The current analysis was based on a hypothetical cohort of commercially insured and Medicare fee-for-service patients with type 2 diabetes who were identified from the NHANES database. Applying the United Kingdom Prospective Diabetes Study (UKPDS) complication risk model to the individual's risk characteristics, the analysis simulated diabetes complication rates under status quo risk factor profiles and complication reductions associated with improved management of A1c, BP, and lipids.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%
“…11 Total health plan costs generated by members with diabetes are largely determined by the size and nature of the patient mix. Patient attributes that can affect health plan spending related to diabetes are listed in Table 4.…”
Section: ■■ the Economic Impact Of Cmr Among Patients With Diabetesmentioning
confidence: 99%
“…[9][10] The annual cost of CVD reportedly ranges from $8,200 to $13,100 per person, depending on the presence of diabetes. 11 In general, spending on individuals with diabetes is substantially higher than spending on those without diabetes. The American Diabetes Association (ADA) estimated that, in 2002, annual per capita medical expenditures were 2.4 times higher for people with diabetes than for similar people without diabetes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…34 The place in therapy for TZDs in type 2 diabetes is summarized clearly and succinctly in the NICE (National Institute for Clinical Excellence) appraisal released in November 2002. TZDs are third-line therapy in type 2 diabetes after sulfonylureas and metformin have proved unsuccessful when used as monotherapy and in combination to achieve glycemic goals.…”
mentioning
confidence: 99%